Changes in Matrix Metalloproteinase-8, Interleukin-6 and Tumor Necrosis Factor-Α in Gingival Crevicular Fluid during Rapid Maxillary Expansion in Adolescent Patients - Zhipeng Tang; Dongxue Mi; Hao Wu; Yanan Fu; Li Liu; Xuelin Chen; Yujia Dong; Weikun Zhang (Tehran University of Medical Sciences, 2021)
Background: Rapid maxillary expansion (RME) is the standard treatment for correcting lateral maxillary defects commonly used in orthodontics. It is the most effective approach to increase maxillary width in clinical practice. At present, there are few studies on the level of molecular biology of periodontal tissue remodeling during RME. We aimed to investigate changes in matrix metalloproteinase (MMP)-8, interleukin (IL)-6 and tumor necrosis factor (TNF)-αin gingival crevicular fluid during RME. Methods: Patients admitted to Department of Stomatology, the Third Affiliated Hospital of Qiqihar Medical University, Qiqihar, Heilongjiang Province, China between Dec 2016 and Dec 2018 were enrolled, and randomly divided into the observation group (76 cases) and control group (62 cases). Periodontal clinical indicators were recorded. Gingival crevicular fluid was collected and the periodontal clinical indicators were recorded. The levels of MMP-8, IL-6 and TNF-α were determined by ELISA, and the contents of the two groups were compared. Results: The plaque index of the observation group was significantly higher than that of the baseline T0 (P< 0.05) from T4, and the increase in the control group started from T5. The general clinical data of the two groups showed that the white blood cell count of the observation group was higher than that of the control group. The levels of MMP-8, IL-6 and TNF-α were the highest at T2, followed by T3, and gradually decreased at T4, and T5, and the differences were significant (P<0.05). Conclusion: The changes in levels of MMP-8, IL-6 and TNF-α in adolescent patients during RME were related to the remodeling of periodontal tissue after RME.